Prevalence of bovine leukemia virus in Colombian cattle as well as the tools to prevent and control it - Uribe, Pablo Juan; Juanes, Fanny Ingrid; Greiff, Álvaro K.; Lopez, Carlos; Pombo, Manolo G. (International Scholars Journals, 2025)
An epidemiological study was conducted to establish the prevalence of the Bovine Leukemia Virus (BLV) in Colombia and to describe risk and protecting factors associated with this infection disease. The study was performed with an observational descriptive cross-sectional process in twelve Colombian regions, by collecting blood samples from 8150 bovines in 390 cattle farms between February and September 2014. The seroprevalence obtained by enzyme-linked immunosorbent assay (ELISA) tests was 42.7% in animals and 67.7% in farms. The highest seroprevalence was found in Villavicencio with 91% in animals. The infection with blood parasites and another virus was attributed to be among the main risk factors associated to BLV. The use of individual needles during veterinary procedures was found to be the main source of protection against the virus. Climate data and ecological groups were recorded at sampling sites in order to elaborate geo-referencing maps by using analyzes of viral distribution around the country. Results obtained showed that there is a probability of an increase on the incidence of this pathology as well as a predictive issue associated with places and climate variables. It was found that developing epidemiological analyzes aiming to report and monitor the presence of this disease and its risk factors is the only alternative to generate prevention and control strategies.